2017
DOI: 10.1007/s11255-017-1761-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of the small renal masses: role of the apparent diffusion coefficient of the diffusion-weighted MRI

Abstract: ADC maps with b values of 0 and 800 s/mm can be used as an imaging biomarker, to differentiate benign SRM from malignant SRM. Using ADC value threshold of 1.75 × 10 mm/s allows to differentiate solid RCC from solid benign kidney tumors with 91% sensitivity and 89% specificity; ADC value threshold of 2.96 × 10 mm/s distinguishes cystic RCC from benign renal cysts with 90% sensitivity and 88% specificity. However, the possibility of differentiation between ccRCC histologic subtypes and grades, utilizing ADC valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
3
13
0
2
Order By: Relevance
“…In our study, all RCC cases showed restricted diffusion, with a mean ADC value of 1.5 ± 0.13×10 -3 mm 2 /s and range of 1.34×10-3 mm2/s -1.74×10 -3 mm 2 /s which is within the range as found in the previous study, with reported ADC values of 1.65 ± 0.38×10 -3 mm 2 /s. 19 However, lower ADC values were also reported in other previous studies. Inci et al surveyed RCC and found that the ADC value was 1.38×10 -3 mm 2 /s at a b value of 1000 s/mm 2 .…”
Section: Renal Cell Carcinomamentioning
confidence: 59%
“…In our study, all RCC cases showed restricted diffusion, with a mean ADC value of 1.5 ± 0.13×10 -3 mm 2 /s and range of 1.34×10-3 mm2/s -1.74×10 -3 mm 2 /s which is within the range as found in the previous study, with reported ADC values of 1.65 ± 0.38×10 -3 mm 2 /s. 19 However, lower ADC values were also reported in other previous studies. Inci et al surveyed RCC and found that the ADC value was 1.38×10 -3 mm 2 /s at a b value of 1000 s/mm 2 .…”
Section: Renal Cell Carcinomamentioning
confidence: 59%
“…anteromedial or perihilar tumour location) or biopsy is relatively contraindicated due to patient factors (single kidney, anticoagulation with a high risk of thrombosis if temporarily withheld). 1,20,27 In many such cases, surgical excision via partial or radical nephrectomy carries significant risk of major complications, quality of life effects and cost/resource burdens on health systems. 28 For these cases, performing an mpMRI that combines T1W, T2W, chemical shift (microscopic fat), diffusionweighted and contrast-enhanced parameters may narrow the differential diagnosis and indicate likely tumour subtype/s.…”
Section: Resultsmentioning
confidence: 99%
“…However, up to 33% of excised or biopsied renal masses have benign or indolent pathology. 1,2 Conventional imaging with CT and US cannot reliably differentiate benign or low-grade malignancies from high-grade malignancies. For example, benign oncocytomas, lipid-poor angiomyolipomas (AMLs) and RCCs can have very similar imaging findings.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 , 8 ] Conventional ultrasound, computed tomography, and magnetic resonance imaging have been widely used to evaluate SRMs. [ 9 12 ]…”
Section: Introductionmentioning
confidence: 99%